Initial hydroxychloroquine monotherapy in systemic lupus erythematosus: report of three cases. (3rd April 2021) - Ichikawa, Kento; Kirino, Yohei; Kunishita, Yosuke; Kishimoto, Daiga; Takase-Minegishi, Kaoru; Yoshimi, Ryusuke; Nakajima, Hideaki
Abstract: Glucocorticoids (GCs) use is associated with increased organ damage in systemic lupus erythematosus (SLE), and the treatment goal is to stop their use. Treatment with hydroxychloroquine (HCQ) without daily GCs may benefit patients by minimising the cumulative dose of GCs, but clinical experience with HCQ monotherapy is limited. To accumulate evidence for initial HCQ monotherapy in SLE, we retrospectively analysed three new SLE patients who visited Yokohama City University Hospital in 2015. The patients were all Japanese females with a mean age of 26.0 ± 5.3 years, high anti-dsDNA antibody titres, no major organ damage, and a mean pre-treatment Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) score of 9.3 ± 3.1. During the mean observation period of 3.8 ± 0.8 years, none of them received daily GCs or immunosuppressants, but one of the three patients were treated with short-term oral GCs and NSAIDs for a skin rash or arthralgia flairs. SLEDAI-2K was reduced to 3.3 ± 1.2. No other new SLE symptoms emerged, and the Systemic Lupus International Collaborating Clinics Damage Index (SDI) of them were maintained at 0. None of the patients developed HCQ-related retinal toxicity. Current experience with initial HCQ monotherapy suggests that such a therapeutic strategy may be useful in managing disease activity and preserving cumulative GCs in SLE patients without organ involvements.